Satu Islam Beda Pemahaman Satu Iman Beda Jalan: Nurcholish Madjid dan Gerakan Pembaruan Pemikiran Islam di Indonesia - Andoni, Yudhi; Qurrata'ayuni Vidhiputri, Shiney (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
This article examines the dynamics of the Islamic renewal movement in Indonesia, with a focus on the thought of Nurcholish Madjid. The research argues that Madjid's thought represents a significant shift from the paradigms of Islamic revivalism and modernism towards neo-modernism, which emphasizes the desacralization of worldly domains and the articulation of Islamic values as a socio-cultural ethic in national life. Using historical research methods with an intellectual history approach, this article analyzes Madjid's controversial 1970 speech,